Syntheses, Characterization and Antioxidant Activity of Some Oxadiazoles - Nimavat, B.; Mohan, S.; Saravanan, J.; Patel, M.P.; Deka, S.; Talukdar, A.; Basak, M.; Sarma, R.K. (Asian Journal of Chemistry, 2012)
Oxadiazole derivatives are an important class of heterocyclic compounds, specifically 2-amino substituted oxadiazoles with biological activities such as antioxidant, anticancer, antibacterial, antifungal, analgesic and antiinflammatory activities. The above observations prompted us to synthesize new oxadiazoles with various substitutions. The starting material 2-amino-5-(3'-acetamidophenyl)-1,3,4-oxadiazole (SBM-4) was synthesized by refluxing a mixture of 3-aminophenol and acetic anhydride in glacial acetic acid. This was followed by refluxing with ethyl chloroacetate and anhydrous K2CO3 in dry acetone, followed by refluxing with hydrazine hydrate in ethanol and the hydrazide was finally treated with CNBr in methanol. The parent compound was then converted to the oxadiazoles by reacting with various substituted aromatic aldehydes. The new compounds were evaluated for in vitro antioxidant activity using ascorbic acid as standard. Among the compounds tested, SBM-4a with 4"-chloro, SBM-4g with 2"-chloro and SBM-4h with 4"-methyl substitution at R showed good antioxidant activity.